Предтечі “Просвіти” - Стеблій, Ф. (Україна: культурна спадщина, національна свідомість, державність, 2010)
Простежено патріотичну працю освічених верств України впродовж багатьох
віків щодо піднесення культурного рівня народу, зокрема внесок у духовну скарбницю гуртків книжників при княжих і єпископських дворах, а також в монастирях часів Київської Русі, культурно-освітню діяльність братств XVI–XVIII ст., культурно-
освітні ініціативи діячів Греко-Католицької Церкви початку ХІХ ст. (спробу заснування Товариства Греко-католицьких священиків у Перемишлі 1816 р.), багатогранну національно-культурно-просвітницьку працю українських романтиків 30–40-х рр. ХІХ ст. (“Руської Трійці”, Кирило-Мефодіївського братства), спалах культурно освітньої діяльності в Галичині під час “Весни народів” (1848–1849) й скликання першого з’їзду діячів науки й культури у Львові (1848) та заснування Галицько-Руської Матиці як науково-культурно-освітнього товариства, яка, однак, незабаром занедбала свою культурно-освітню функцію, поступившися місцем “Просвіті”. The author traces patriotic work of the educated strata of Ukraine through the
centuries that was aiming at the elevation of the cultural level of the people, in particular
the contribution of the circles of bookmen at princely and bishopric courts and also in
the monasteries of Kievan Rus’ period, cultural-educational activities of brotherhoods
of the 16–18th centuries, cultural-educational initiatives of the members of the Greek
Catholic Church at the beginning of the 19th century (attempt at establishing Society of
Greek Catholic priests in Peremyshl’ in 1816), manifold national cultural-enlightening
work of Ukrainian romantics in the 1830s–40s (“Ruthenian Triad”, Cyrill and Methodius
Society), acceleration of cultural-educational activities in Galicia during the “Spring
of Nations” (1848–1849) and convention of the first Congress of men of science and
culture in Lviv (1848) and establishing of the Galician-Ruthenian Matytsia as scholarly
cultural-educational society that soon neglected its cultural-educational functions and
was replaced by the “Prosvita” society.